Patterns of regional income inequality in Egypt: Implications for sustainable development goal 10 - Ioannis Bournakis; Mona Said; Antonio Savoia; Francesco Savoia (Luxembourg Income Study (LIS), 2020)
Income distribution is seen as instrumental to human development and to a number of development outcomes through a variety of channels. It is also considered important in itself, as testified by its inclusion in the Sustainable Development Goals. Yet existing research on income inequality in developing economies has not devoted much attention to the regional dimension. This is important, as progress in reducing income inequality at national level on SDG Goal 10 is only a partial success if a country presents large regional variation, where very unequal regions coexist alongside relatively equal ones. This paper contributes to fill this gap by offering a case study on Egypt, and adds to our knowledge of income inequality in the Arab region, an area that has not seen extensive empirical analysis. Using newly assembled data by LIS and a range of inequality measures, the paper shows that there has generally been an increase in income inequality during 1999-2015 and finds evidence of unconditional convergence in income distribution across Egyptian Governorates. This result implies that income inequality in less unequal regions grows faster than in more equal regions, regardless of regional characteristics. Second, the speed of convergence has not been uniform: sustained for most regions, but significantly slower or even lacking for some regions. Finally, convergence across regions has been significant also for the bottom forty per cent and proportion of people living below 50% median income, implying that maintaining this convergence process will be an important policy avenue to guarantee that progress on SDG 10 will be geographically widespread, achieving shared prosperity at both the national and regional level.
Keywords: O15; D63; 330; income distribution; convergence; regional disparities; SDG Goal 10; development goals; social conflict; Luxemburg Income Study